q-Analog of Gelfand-Graev Basis for the Noncompact Quantum Algebra Uq(u(n,1)) - Asherova, R.M.; Burdík, Č.; Havlíček, M.; Smirnov, Y.F.; Tolstoy, V.N. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
For the quantum algebra Uq(gl(n+1)) in its reduction on the subalgebra Uq(gl(n)) an explicit description of a Mickelsson-Zhelobenko reduction Z-algebra Zq(gl(n+1),gl(n)) is given in terms of the generators and their defining relations. Using this Z-algebra we describe Hermitian irreducible representations of a discrete series for the noncompact quantum algebra Uq(u(n,1)) which is a real form of Uq(gl(n+1)), namely, an orthonormal Gelfand-Graev basis is constructed in an explicit form.